2009
DOI: 10.1080/01480540903170720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium monofluoroacetate on glucose, amino-acid, and fatty-acid metabolism and risk assessment of glucose supplementation

Abstract: Sodium monofluoroacetate (SMFA; also known as compound 1080) is a highly toxic chemical; therefore, accidental exposure and intentional misuse are of great concern. SMFA intoxication is reportedly caused by the inhibition of aconitase. However, the pathogenesis underlying SMFA intoxication is not clear. This study was conducted to elucidate the acute effects of SMFA on glucose, amino-acid, and fatty-acid metabolism and to assess glucose supplementation as a possible alleviator or aggravator in SMFA intoxicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…GLU is considered to be one of the key substances most affected by FAcOH intoxication; however, the mechanism is not clear. 2 In our study, the mean value of GLU in different groups (convulsion, unconsciousness or death) was higher than the control group, which indicated that FAcOH could induce an imbalance in GLU. This may be due to the accumulation of citrate in vivo, which can inhibit the activity of phosphofructokinase, a key enzyme in glycolysis.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…GLU is considered to be one of the key substances most affected by FAcOH intoxication; however, the mechanism is not clear. 2 In our study, the mean value of GLU in different groups (convulsion, unconsciousness or death) was higher than the control group, which indicated that FAcOH could induce an imbalance in GLU. This may be due to the accumulation of citrate in vivo, which can inhibit the activity of phosphofructokinase, a key enzyme in glycolysis.…”
Section: Discussionmentioning
confidence: 43%
“…The use of these two rodenticides has been severely restricted in many countries due to their high toxicity to human and animals. 1,2 However, driven by economic interests, the illegal production and sale of these rodenticides still exist in some developing countries. 3 Several suicide poisoning cases with these rodenticides continue to be reported in recent years.…”
Section: Introductionmentioning
confidence: 99%